PERSEPSI GURU PJOK DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SECARA DARING DI SMA NEGERI KECAMATAN MANDAU DURI - Jimmy Gunawan Butar Butar; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the teacher's perception of PJOK in learning PJOK online at SMA Negeri Mandau Duri District. Based on the results of the research, it shows that (1) PJOK teacher perceptions in online PJOK learning on student motivation in implementing physical education learning at SMA Negeri Mandau Duri District, that there are 13 (81%) students who are in good criteria. (2) Teacher's Perception of PJOK In online PJOK learning on the ability of teachers in implementing physical education learning at SMA Negeri Mandau Duri District, that there are 10 (63%) students who are in the Enough criteria. (3) Teacher's Perception of PJOK In online learning of PJOK at SMA Negeri Mandau Duri District on the completeness of facilities and infrastructure there are 9 (56%) students who are in good criteria. Thus the perception of PJOK teachers in online PJOK learning at SMA Negeri Mandau Duri District is seen from the overall data of sub-variables consisting of, a). Motivation, b). Orchestra Physical Education teacher, c). Facilities and infrastructure can be said to be quite good, with a percentage (81%) and (56%) these results mean that the perception of PJOK teachers in online PJOK learning at SMA Negeri Mandau Duri District has been able to run well.Key Words: Teacher Perception, PJOK Online Learning